(untitled) (Homoeopathy for All, 2022)
Acne is one of the most familiar skin complaints encountered by millions of people of all ages, colours and skin types.1 For many suffering from acne seems a never ending process. It is estimated that more than 85% of adolescents suffer from it and it extends into adulthood in approximately.2 50% of cases. The location (on the face) the acne appears, make it more troublesome for the sufferer. Research suggests that acne affects mental health and leads to anxiety, stress, depression, poor self-confidence and social isolation. As per the recent studies in the dermatology clinic, 25%-43% of patients visit have a psychological disorder.3,4 The comorbidity of depression and skin diseases is around 30%.5 The study also found that stress is one of the aggravating conditions of skin diseases.6 Conventional treatments have limited scope in the management of acne. Usually, they focus on inhibiting sebum production, limiting bacterial growth, encouraging the shedding of skin cells to unclog pores, or a newer treatment that blocks male hormones in the skin. It is known to all that such treatment has long-term side effects. In this article, we have focused on the association of acne with psychology and the efficacy of homoeopathy treatment in the management of acne along with the change in the quality of life.